Policy to Practice. (January 2015) - Gasparini, Robin; Champagne, Mary; Stephany, Alyssa; Hudson, John; Fuchs, Mary Ann
<x xml:space="preserve">Abstract</x> Objective: This quality improvement study introduced 24/7 family presence and measured its impact in 3 categories; perceptions, complaints, and patient experience scores. This article offers insight for leaders into the 1st phase of patient- and family-centered care (PFCC) adoption. Background: Family presence improves patient safety and satisfaction; however, 70% of US healthcare organizations maintain restrictive visitation policies. Methods: We surveyed nursing staff 6 months postinnovation to determine staff knowledge, implementation practices, and perceived challenges to implementation. We surveyed system leaders regarding PFCC transformation and trended formal complaints and patient experience scores after family presence innovation. Results: Findings provide insight for leaders into family presence policy adherence challenges experienced by staff. Leaders perceived significant transformation toward PFCC adoption postinnovation. Complaints increased postinnovation, and patient experience scores demonstrated positive trends. Conclusions: We gained insight regarding challenges to policy adherence and identified next steps for leaders in the transformation toward PFCC adoption.